Elucidating the nanoscopic organization and dynamics of the nuclear pore complex - Kevin N. Baumann; Eva Bertosin; Anders Barth; Cees Dekker; Roderick Y.H. Lim (Nucleus)
Due to its pivotal role as a regulator of nucleocytoplasmic transport, the structure and dynamic gating mechanism of the nuclear pore complex (NPC) is a subject of immense interest. Here, we report key recent advancements discussed at the Selective Transport Control in Biological and Biomimetic Nanopores meeting (Monte Verità, Switzerland, 2024) that gathered NPC experts from a range of disciplines. Novel insights were reported from cutting-edge super-resolution techniques that enable the direct interrogation of the NPC’s dynamic central transporter; computational models that unravel the mechanisms of the selective barrier; and synthetic NPC mimics as valuable in vitro models for delineating NPC permeability and transport dynamics. Altogether, three major insights were highlighted: (i) the presence of dynamically organised nuclear transport pathways within the NPC, (ii) the role of nuclear transport receptors that enrich and reinforce the NPC’s selective permeability barrier, and (iii) the ability of DNA origami nanostructures to mimic aspects of the NPC with unprecedented precision. Overall, the advancements marked a convergence in our understanding of NPC function by unraveling its dynamic gating mechanism at the nanoscale.